REORIENTASI MANAJEMEN PENDIDIKAN ISLAM DI ERA DIGITAL: : PENGUATAN KESEHATAN MENTAL MAHASISWA MELALUI PENDEKATAN DIGITAL WELL-BEING - abdul kholiq abdul kholiq (Institut Agama Islam Ngawi, 2025)
The rapid development of digital technology has significantly transformed students' learning patterns, communication, and lifestyles. While digital technology offers various educational benefits, excessive and uncontrolled use may contribute to mental health issues, including anxiety, digital fatigue, fear of missing out (FoMO), and decreased psychological well-being. This study aims to analyze the concept of digital well-being and explore its integration into Islamic Educational Management as a strategic approach to promoting students’ mental health. This research employed a library research method by examining scholarly articles, books, and relevant scientific publications related to digital well-being, mental health, and Islamic education. The data were analyzed using content analysis techniques to identify key themes and conceptual relationships. The findings reveal that digital well-being aligns with Islamic educational values emphasizing balance, self-regulation, responsibility, and moderation in technology use. The study proposes a conceptual model of Islamic Educational Management based on digital well-being through digital literacy strengthening, mental health support services, ethical digital governance, and spiritual development programs. This model is expected to contribute to creating a healthier, more balanced, and sustainable digital learning environment for university students.